Urinary tract diversion with gastric conduit after total pelvic exenteration for Crohn’s disease-related anorectal cancer: a case report - Kei Kimura; Akihiro Kanematsu; Masato Tomono; Kozo Kataoka; Naohito Beppu; Motoi Uchino; Hisashi Shinohara; Hiroki Ikeuchi; Shingo Yamamoto; Masataka Ikeda (Surgical Case Reports)
Abstract Background In Japan, Crohn’s disease (CD)-related cancers occur most frequently in the anal canal. Many patients with advanced CD-related cancer require total pelvic exenteration (TPE) based on their medical history, and choosing the most effective method for urinary diversion is a major concern. We herein report the first case of CD-related cancer treatment with urinary diversion using a gastric conduit after TPE in Japan. Case presentation A 51-year-old man with a 25 year history of CD was referred to our institution after having been diagnosed with fistulae between the rectum and urethra. Sigmoidoscopy revealed stenosis of the anal canal, and histological examination of this lesion led to a diagnosis of mucinous adenocarcinoma. Magnetic resonance imaging showed that the tumor had invaded the prostate and left internal obturator muscle, and TPE with left internal obturator muscle resection was planned. Urinary diversion was performed with a gastric conduit. The gastric conduit was created by trimming a gastric tube to a 1.5 cm width via stapled resection of the greater curvature, and the branches of the right gastroepiploic artery were preserved as feeding vessels. The ureters were raised from the mesentery on the right side of the ligament of Treitz. Ureterogastric anastomosis was performed using the Wallace technique, and the entire anastomosis was then retroperitonealized. The anastomotic site had a bleeding tendency, but hemostasis was obtained by proton pump inhibitor administration and discontinuation of enoxaparin, which had been administered to prevent venous thrombosis. No other major complications occurred, and the patient’s quality of life was recovered 6 months after surgery. Conclusion Urinary diversion using a gastric conduit is a feasible treatment option for patients with CD-related anorectal cancer requiring TPE.